The problems of Physical Education training: selfregulation development of pupils and students - Переверзєва, Світлана Василівна (Pedagogy of Higher and Secondary Education, 2015)
Pereverzeva S. V. The problems of Physical Education training: selfregulation development of pupils and students. In the article the intentional development of Physical Education focused on pedagogical process, which consists of implenetation of effective ideas, forms of teacher’ educational activities using person centered training of pupils and students was grouned. The educational activity system with application of conceptual provisions and principles was analysed.